An investigation into whether poaching creates an ecological trap for white rhinoceros in Hluhluwe-iMfolozi Park, South Africa - Michel, Alice (SLU/Dept. of Wildlife, Fish and Environmental Studies, 2019)
In an ecological trap, animals choose habitat based upon cues that once led members of their species to optimal habitat, but now lead to habitat where individual fitness is reduced because of changing conditions. The southern white rhinoceros (Ceratotherium simum) is a threatened species due to poaching for its keratin horn. Here, I investigate the degree to which poaching creates an ecological trap for white rhinoceros in South Africa’s Hluhluwe-iMfolozi Park. To this end, I develop a model for white rhino habitat preference and analyse rhino movement through time over the gradient of habitat preference and poaching risk. Three aspects of the ecological trap scenario were assessed: environmental habitat quality in hotspots relative to cold-spots for poaching, rhino movement into high-quality habitat regardless of poaching risk, and the impact of poaching on white rhino fitness at the population level. I found that while high quality habitat exists in poaching hotspots, net colonization was higher into high quality habitat in low-risk areas for poaching than in high-risk poaching hotspots. Further, fitness has declined for rhino populations in hotspots relative to cold-spots of the same quality, and likely represents a loss in fitness to the park population as a whole. While at this time there is little evidence to suggest rhino are pulled away from high quality cold-spots to areas at high risk for poaching, continued monitoring of the habitat quality-risk gradient is crucial to understanding and managing the white rhino population in Hluhluwe-iMfolozi Park.